Redes de apoio e inclusão escolar: implicações de cuidadores na inclusão de estudantes público-alvo da educação especial - Vargas, Paulo Roberto Bellotti (2021)
The purpose of this work was to constitute continuous-formation moments with professionals working at the Education Board of Castelo, ES, Brazil, in order to discuss the assignment of caretakers in schooling-support networks for special-education target-public students, problematizing implications on teaching-learning processes in ordinary schools. It is grounded on the Brazilian education legislation since the promulgation of the Citizen Constitution (BRASIL 1998;1996; 2011; 2015), because of undeniable advancements it has provided for the recognizance of Education as a general right, Special Education as a teaching modality, and specialized educational assistance as complementary/supplementary schooling for students with deficiencies, global development disorders, and high abilities/super-endowment. Boaventura de Sousa Santos’ theoretical contributions have also been used, besides those of Special Education authors (KASSAR & RABELO, 2011; BAPTISTA, 2011; JESUS, 2006; RAMOS, 2013; VIEIRA, 2012, 2015), constituting knowledge about schooling-support networks for the acknowledgement of the pedagogical work as an attribution of both ordinary school and Special Education teachers, with the support of the caretakers for nourishment, hygiene, and locomotion, without substitution or overlapping of functions, but collaboration actions instead. Qualitative research and critical-collaborative research-action supported this work. Data-collection comprised: a) Asking the competing organ permission for the conduction of this assessment; b) browsing documents concerning Education and Special Education policies of Castelo, ES, Brazil; c) constitution of formation processes; d) interview with a pedagogue. This involved the Municipal Education Board Secretary, one social worker, one psychologist, seven pedagogues, and one History teacher serving directly at the Municipal Board. Data have been collected from August to December 2019, having field log and voice recorders as registration instruments. It conveys the importance of policies supporting the schooling of Special Education target-public students without replacing Special Education teachers by caretakers, recognizing at the same time the functions of the latter in support-activities (holding sight at the pedagogical action along the process); of investing in actions that prioritize the constitution of support-networks for Special Education target-public students, composed by several professionals: regent teachers, Special Education teachers, pedagogues, caretakers, among others, without substituting functions, indulging precariousness, or negating the pedagogical support for the teaching process; of recognizing the investment in the formation of management staffs, the place they hold in the formulation of education policies, mainly through the necessity of tightening bonds in the act of caring, yet, keeping ethically committed with education and the right to learn.